Influence Of Distributive, Procedural And Interactional Justice On Employee Satisfaction (Case Study In The National Parliament Of Timor-Leste) - Teresa Cardoso Gomes; I Gede Riana; Pedro Miguel Barreto Ximenes (LPPM Institut Teknologi dan Sains Mandala, 2022)
Role and Organization The National Parliament of Timor-Leste is a sovereign body which is constitutionally established